PERAN FATHIMAH BINTI ABDUL WAHAB BUGIS DALAM PENULISAN KITAB PARUKUNAN MELAYU - Saifuddin, Saifuddin (JURNAL PENELITIAN KEISLAMAN, 2011)
In general, female ulama (scholars) have not received acknowledgment in the tradition of Islamic scholarship despite the fact that many female ulama play an important role in the field. There has been reluctance to admit the female author. Not surprisingly, Fathimah binti Abdul Wahab Bugis, who originally authored Parukunan Melayu, is neglected precisely because her name does not appear in the book, since the bookâs authorship is often associated with a male ulama, namely Mufti JamÃ¢luddÃ®n. This article aims to uncover the role of Fathimah in writing the book Parukunan Melayu. Through historical and documentary methods, the study demonstrates that the book was written by Fathimah and yet female voices have a little weight in the work. There is a great part of the work that just repeats what has been echoed in the works of al-Sayyid al-âAlawÃ®, Syekh Muhammad Arsyad, and Syekh NÃ»r al-DÃ®n al-RÃ¢nÃ®rÃ®. This does not mean, however, that there is simply no voice for women. It is likely that FÃ¢thimahâs thought have been reflected in the work. However, based on intertextuality analysis, such thoughts are not typical of Fathimahâs, but are derived from her predecessorsâ among ulama. Keywords